1990
DOI: 10.1021/ac00210a014
|View full text |Cite
|
Sign up to set email alerts
|

Laser desorption/ionization Fourier transform mass spectrometry and fast atom bombardment spectra of nonvolatile polymer additives

Abstract: Laser desorption Fourier transform mass spectra (LD-FTMS) of a variety of nonvolatile polymer additives are compared with fast atom bombardment spectra (FAB) of the same materials. Both a pulsed carbon dioxide laser and a neodymlum-YAG laser with outputs of 10.6 and 1.064 Mm, respectively, were used to obtain LD-FTMS spectra of all samples. Three sterlcally hindered phenols and other additives containing a variety of functionalities Including thloester, phosphite, phosphonlte, and hindered amine groups were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…As the UV light interacts with the SP film, a second set of peaks appears (Figure 9, middle). These peaks, shifted down by 284 amu, are attributed to the formation of an acid fluoride end group, -CFO, at the first ether oxygen from the end according to the following overall reaction R,-(CF2CF2CF2-0)m-CF2CF2C00-CH2CH2-0-C6H5 -R,-(CF2CF2CF20)w_1-CF2CF2CF0 + CF3CF2C00-CH2CH2-0-C6H5 (7) The ion observed is the Cu+-cationized acid fluoride. As the film is exposed to even more UV radiation, only the acid fluoride end groups are left in the mass spectrum (Figure 9, bottom).…”
Section: Resultsmentioning
confidence: 99%
“…As the UV light interacts with the SP film, a second set of peaks appears (Figure 9, middle). These peaks, shifted down by 284 amu, are attributed to the formation of an acid fluoride end group, -CFO, at the first ether oxygen from the end according to the following overall reaction R,-(CF2CF2CF2-0)m-CF2CF2C00-CH2CH2-0-C6H5 -R,-(CF2CF2CF20)w_1-CF2CF2CF0 + CF3CF2C00-CH2CH2-0-C6H5 (7) The ion observed is the Cu+-cationized acid fluoride. As the film is exposed to even more UV radiation, only the acid fluoride end groups are left in the mass spectrum (Figure 9, bottom).…”
Section: Resultsmentioning
confidence: 99%
“…Of the ions produced in Figure 1, the process leading to formation of [TPP + K]+ at mjz 653 is most studied and best understood because it is also the vehicle by which most infrared LDIjtime-of-flight and LDIjFT-ICR mass spectra of organic molecules are produced [38][39][40][41][42][43][44]. Specifically, a weak ionic association results from the gas-phase ion-molecule reaction [20][21][22][23]35] between an intact neutral TPP and a precursor ion from the salt.…”
Section: General Features Of Tetraphenylporphyrin Spectramentioning
confidence: 99%
“…Also, these techniques deposit large amounts of energy at the sample surface and typically generate predominantly fragment ions of the polymer itself. Laser desorption (LD) and laser desorption/Fourier-transform ion cyclotron resonance (LD-FTICR) mass spectrometry have also been applied with considerable success to the detection of many classes of nonvolatile compounds including organic polymers. Johlman et al demonstrated that LD-FTICR could be used to identify polymer additives in polyethylene extracts. The spectra were found to contain intense quasimolecular ions (Na + and K + adducts) as well as fragments. …”
Section: Introductionmentioning
confidence: 99%